Sensory profile and acceptability of traditional and double-distilled cachaca aged in oak casks - Rota, Michelle Boesso [UNESP]; Piggott, John Raymond [UNESP]; Faria, João Bosco [UNESP] (Inst Brewing, 2013)
Distillation is an important step to obtain a beverage of good quality, because it separates, selects and concentrates the components of the wine, as well as promoting some chemical reactions induced by the heat. Thus the volatile components of the wine can increase or decrease, or new components can even be produced. Recently, the technique of double distillation has been implemented to restructure the profile of organic compounds of sugar cane spirits produced in pot stills, with the aim of obtaining a sensorially differentiated product. In addition to the distillation, the ageing process is a key step in improving the quality of cachaca. This study aimed to describe the sensory profile of six samples of cachaca, with variations in the kind of distillation (traditional and double distillation) and ageing for 12 and 24 months in oak casks. The sensory profile was performed by descriptive analysis by a panel of nine trained assessors, using 18 terms to describe the similarities and differences between the samples. An acceptance test with 60 panellists, potential consumers of aged and non-aged cachaca, was also completed. The descriptors used revealed differences in the sensory profiles between the traditional and double-distilled samples, and that the double-distilled samples showed greater intensity of the attributes related to ageing in oak casks. Acceptance testing also showed a greater consumer preference for the double-distilled aged samples. Copyright (C) 2013 The Institute of Brewing & Distilling
Keywords: double distillation; descriptive analysis; acceptance test; maturation; sugar cane spirit